Introduction to Computer Ethics - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Ethics is becoming one of the most often used but also misinterpreted wordс. It is often taken as an additional, corrective parameter  to the policies and strategies  that has to be adopted in the area of ​​political works, environment, business, and medicine. Computer ethics thus makes the latest ethical discipline in the scientific sky. But its roots, as  it was the case with environmental ethics, ranging decades; only the speech and the use of the same, as well as discussions on the postulates of computer ethics,  are the results of rapid IT development in the last decade or two. In this paper, according to the title, will be shown introduction to computer ethics-its basis, the most important representatives, as well as the most important suc-sion.